Exponential Function: a proposal for mathematical tasks - Ferreira, Rodrigo dos Santos; Pereira da Costa, André (Educação Matemática Debate, 2024)
The purpose of this work has been to propose mathematical tasks involving the exponential function using the GeoGebra software. Thus, it has been based on the discussion about mathematical tasks by João Pedro da Ponte and the Theory of Semiotic Representation Registers. This is a qualitative explanatory research as regards its aims and it has been based upon bibliographical survey and assessement of the sources. Its development has involved the elaboration and adaptation of tasks through testing in the GeoGebra, followed by the writing of a set of didactical guidelines to teachers. The GeoGebra has been proved to be a suitable didactical resource for proposing tasks on exponential functions by enabling an experimental character in the classroom, which could provide High School students with autonomy in studying this mathematical concept.